HUBUNGAN ANTARA EMOTIONAL LABOR DENGAN PSYCHOLOGICAL WELL-BEING PADA PERAWAT RUMAH SAKIT X LAMPUNG UTARA - Shakahagaya, Vika Esya; Syah, Tansri Adzlan; Setriani, Setriani (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Nurses have a major contribution to the health sector, both physically and mentally. In their duties, nurses are required to display emotions according to institutional expectations, a process known as emotional labor. This study examines the relationship between emotional labor and psychological well-being among nurses at X Hospital in North Lampung. The research employed a quantitative method with a total sample of 70 nurses out of 73 available. The instruments used were the Emotional Labor Scale consisting of 27 items (? = 0.930) and the Psychological Well-Being Scale with 20 items based on the PERMA theory (? = 0.850), using a four-point Likert scale. Data were analyzed using SPSS 25.0 to test normality, reliability, linearity, and Pearson correlation. The results showed a significant positive correlation between emotional labor and psychological well-being (r = 0.293; p = 0.014). This finding highlights the importance of effective emotional management for nurses’ mental health.